2005
DOI: 10.1371/journal.pbio.0030096
|View full text |Cite
|
Sign up to set email alerts
|

Two Distinct E3 Ubiquitin Ligases Have Complementary Functions in the Regulation of Delta and Serrate Signaling in Drosophila

Abstract: Signaling by the Notch ligands Delta (Dl) and Serrate (Ser) regulates a wide variety of essential cell-fate decisions during animal development. Two distinct E3 ubiquitin ligases, Neuralized (Neur) and Mind bomb (Mib), have been shown to regulate Dl signaling in Drosophila melanogaster and Danio rerio, respectively. While the neur and mib genes are evolutionarily conserved, their respective roles in the context of a single organism have not yet been examined. We show here that the Drosophila mind bomb (D-mib) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
210
1
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(236 citation statements)
references
References 62 publications
(78 reference statements)
17
210
1
8
Order By: Relevance
“…5BЉ), but not with Mib1 (Fig. 5C Љ), another E3 ligase that promotes the endocytosis of Delta (12,13,36,37). In contrast to Neur2, Mib1 did not co-localize with Hrs (Fig.…”
Section: Neur2 Is a Neur1 Paralog-the Drosophila And Xenopusmentioning
confidence: 94%
“…5BЉ), but not with Mib1 (Fig. 5C Љ), another E3 ligase that promotes the endocytosis of Delta (12,13,36,37). In contrast to Neur2, Mib1 did not co-localize with Hrs (Fig.…”
Section: Neur2 Is a Neur1 Paralog-the Drosophila And Xenopusmentioning
confidence: 94%
“…Drosophila Delta has in its intracellular region monoubiquitination motifs which can be targeted by Neuralized and Mind bomb1 (Le Borgne et al 2005b). The bearded gene family (brd) antagonizes Neuralized activity (Bardin & Schweisguth 2006).…”
Section: Lateral Inhibitionmentioning
confidence: 99%
“…These and other observations [106,161] suggested that an endocytic event could precede Notch activation. Direct evidence in support of this hypothesis came from (i) antibody uptake assays in living Drosophila tissue and in mammalian cells, which showed that DSLs are rapidly and efficiently internalized upon antibody binding and clustering [162][163][164], (ii) transfection assays with endocytosis-defective DSLs, which provided direct evidence that Notch ligand internalization is required to activate Notch signaling [164,165], and (iii) uptake assays of recombinant forms of DSL (Delta1-Fc chimeric protein) [166] and of Notch-1 (N1Fc chimeric protein) [167], which showed that even soluble fragments of Notch ligands and Notch receptors, upon clustering, could potently promote the internalization of their cognate partners. Under these conditions, the Delta1-Fc chimera was also proved to be able to fully activate canonical Notch signaling [166].…”
Section: Endocytosis In Notch Signaling Activationmentioning
confidence: 99%
“…Mib encodes for another RING-type E3 ligase, whose loss-of-function mutants cause major Notch developmental defects in the Danio R. [164]. Mib and Neuralized show complementary functions: (i) as for Neur, Mib(s) act(s) in the signal-sending cell [164] by promoting endocytosis of various DSLs, including Xenopus Delta [243] and Zebrafish Delta [164]; (ii) two mib genes are present in Drosophila with tissue distribution that complements that of Neur: inactivation of Mib indeed caused Notch defects in flies, but only in those tissues in which Neur was not expressed, while in tissues in which both Neur and Mib(s) were expressed, Notch phenotypes arose only upon co-inactivation of all E3 ligases [162,[243][244][245]. (iii) Mib1 cannot rescue Drosophila neur mutants [162], and, conversely, Neur and Mib1 cannot compensate for mib2 defects in myoblast fusion and muscle homeostasis [246], thus showing that Mib(s) and Neur probably have other functions besides the ubiquitylation of DSL substrates.…”
Section: Specialized Endocytic Machinerymentioning
confidence: 99%